(3GdYed HPGJ GdMdb aj Yde GdgjFIs ((3YHO Gdbhi Hf YHO GdeYWi Hf gdGd Hf YWjI Hf Jeje Hf GdeYR Hf HGOjS GdCfUGQj s)
(3ChdgG (B:s
(3QSGdI ai GdYed HGdBdI GdadcjI GdeYQhaI HfGJ GdMdb hGdBdGJ GdJi YedgG GdChdhf hPcQJ dc CfhGY PGJ GdUaGFM GdJi gh GdCSWQdGH s
(3BNQgG (B:s
(3aeG Hbi agi SGYGJ eZjHI JMJ GdCQV hJdc SGYGJ djdg Ef TGA Gddg JeJ CHhGH Gdaf GdKGfi ef gPg GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG QShe adcjI HChdgG hba GdcJGH ef GdSdWGf GdYKeGfi eMehO NGfs
(3cJH HgG GdeDda Edi CHj GdMSf eMeO Hf GdMSjf cJHJ HNW eged GdfbW bdjdkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(4861(1)) s
Keywords: (3Gdadcs